The Transcriptome Landscape of Walnut Interspecies Hybrid (Juglans hindsii × Juglans regia) and Regulation of Cambial Activity in Relation to Grafting - Ma, Qingguo; Bu, Dechao; Zhang, Junpei; Wu, Yang; Pei, Dong (Frontiers in Genetics, 2019)
Walnuts (Juglans, Juglandaceae) are known throughout the world as economically important trees that provide fat, protein, vitamins, and minerals as a food source, and produce high-quality timber. We have amended the purpose section to say “However,” the omics resources are limited, which hampered the elucidation of molecular mechanisms resulting in their economically important traits (such as yield, fertility alternation, oil synthesis, and wood formation). To enrich the omics database of walnut, there is great need for analyses of its genomic and transcriptomic characteristics. In this study, we reported for the first time of the transcriptome landscape of six important organs or tissues in walnut interspecies hybrid using next-generation sequencing technology. Over 338 million clean reads were obtained. This yielded 74,072 unigenes with an average length of 782.71 bp. To develop an understanding of gene functions and regulatory pathways, 66,355 of the unigenes were identified as homologs of annotated genes and classified into three general categories with 61 functional subcategories. 2,288 out of 2,549 unmapped unigenes had at least one BLAST hit against the public databases. A total of 1,237 transcription factor-encoding genes (TFs) and 2,297 tissue-specific unigenes were identified. Interestingly, in the new shoot between an adult seedling and a grafted tree, the expression of 9,494 unigenes were significantly different, among which 4,388 were up-regulated and 5,106 were down-regulated. Of these, 195, 177, 232, 75, 114, and 68 unigenes were related to transcription factors, cell wall, defense response, transport, plant hormone biosynthesis, and other cambial activity-related functions, respectively. The obtained sequences and putative functional data constitute a resource for future functional analyses in walnut and other woody plants. These findings will be useful in further studies addressing the molecular mechanisms underlying grafting-related cambial activity.